Reset your child's brain eaudiobook A four-week plan to end meltdowns, raise grades, and boost social skills by reversing the effects of electronic screen-time. - Dunckley, MD, Victoria L. (Tantor Media, 2018)
Increasing numbers of parents grapple with children who are acting out without obvious reason. Revved up and irritable, many of these children are diagnosed with ADHD, bipolar illness, autism, or other disorders but don't respond well to treatment. They are then medicated, often with poor results and unwanted side effects. Based on emerging scientific research and extensive clinical experience, integrative child psychiatrist Dr. Victoria Dunckley has pioneered a four-week program to treat the frequent underlying cause, Electronic Screen Syndrome (ESS). Dr. Dunckley has found that everyday use of interactive screen devices—such as computers, video games, smartphones, and tablets—can easily overstimulate a child's nervous system, triggering a variety of stubborn symptoms. In contrast, she's discovered that a strict electronic fast single-handedly improves mood, focus, sleep, and behavior, regardless of the child's diagnosis. Offered now in this book, this simple intervention can produce a life-changing shift in brain function—all without cost or medication. Dr. Dunckley provides hope for parents who feel that their child has been misdiagnosed or inappropriately medicated, by presenting an alternative explanation for their child's difficulties and a concrete plan for treating them.